Offside : soccer and American exceptionalism - Markovits, Andrei S.; Hellerman, Steven L., 1958- (Princeton studies in cultural sociology., 2001)
Soccer is the world's favorite pastime, a passion for billions around the globe. In the United States, however, the sport is a distant also-ran behind football, baseball, basketball, and hockey. Why is America an exception? And why, despite America's leading role in popular culture, does most of the world ignore American sports in return? Offside is the first book to explain these peculiarities, taking us on a thoughtful and engaging tour of America's sports culture and connecting it with other fundamental American exceptionalisms. In so doing, it offers a comparative analysis of sports cultur.